Development of a tetravalent subunit vaccine against dengue virus through a vaccinomics approach - Basheer, Amina; Jamal, Syed Babar; Alzahrani, Badr; Faheem, Muhammad (Frontiers in Immunology, 2023)
Dengue virus infection (DVI) is a mosquito-borne disease that can lead to serious morbidity and mortality. Dengue fever (DF) is a major public health concern that affects approximately 3.9 billion people each year globally. However, there is no vaccine or drug available to deal with DVI. Dengue virus consists of four distinct serotypes (DENV1-4), each raising a different immunological response. In present study, we designed a tetravalent subunit multi-epitope vaccine, targeting proteins including structural proteins envelop domain III (EDIII), precursor membrane proteins (prM), and non-structural protein (NS1) from each serotype by employing an immunoinformatics approach. Only conserved sequences obtained through multiple sequence alignment were used for epitope mapping to ensure efficacy against all serotypes. The epitopes were shortlisted based on IC50<50, antigenicity, allergenicity, and toxicity analysis. In a final vaccine construct, overall, 11 B cell epitopes, 10 HTL epitopes, and 10 CTL epitopes from EDIII, prM, and NS1 proteins targeting all serotypes were selected, and joined via KK, AAY, and GGGS linkers respectively. We incorporated 45 amino acids long B-defensins adjuvant in final vaccine construct for a better immunogenic response. The vaccine construct has shown an antigenic score of 0.79 via VaxiJen and has shown to be non-toxic and non-allergenic. Our refined vaccine structure has a Ramachandran score of 96.4%. The vaccine has shown stable interaction with TLR3 that has been validated by 50ns of molecular dynamics (MD) simulation. Our findings propose that a designed multi-epitope vaccine has substantial potential to elicit a strong immune response against all dengue serotypes without causing any adverse effects. Furthermore, the proposed vaccine can be experimentally validated as a probable vaccine suggesting it may serve as an effective preventative measure against dengue virus infection.